Binding energy of excitons in parabolic quantum wells in uniform electric and magnetic fields - Taqi, A.; Diouri, J. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2012)
Parameterized equations have been derived using variational calculation for energy levels of Wannier excitons in 2D-parabolic quantum wells in uniform electric and magnetic fields. The formulation has been performed in the framework of the effective mass approximation and two-band model. Illustrations have been given for GaAlAsGaAs-GaAlAs and CdMnTe-CdTe-CdMnTe parabolic quantum wells. The comparison with existing data displays good agreement.